Macrocyclic Chelates Bridged by a Diaza-Crown Ether: Towards Multinuclear Bimodal Molecular Imaging Probes - Gaoji Wang; Goran Angelovski (Molecules, 2020)
Bridged polymacrocyclic ligands featured by structurally different cages offer the possibility of coordinating multiple trivalent lanthanide ions, giving rise to the exploitation of their different physicochemical properties, e.g., multimodal detection for molecular imaging purposes. Intrigued by the complementary properties of optical and MR-based image capturing modalities, we report the synthesis and characterization of the polymetallic Ln(III)-based chelate comprised of two DOTA-amide-based ligands (DOTA—1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid) bridged via 1,10-diaza-18-crown-6 (DA18C6) motif. The DOTA-amide moieties and the DA18C6 were used to chelate two Eu(III) ions and one Tb(III) ion, respectively, resulting in a multinuclear heterometallic complex Eu2LTb. The bimetallic complex without Tb(III), Eu2L, displayed a strong paramagnetic chemical exchange saturation transfer (paraCEST) effect. Notably, the luminescence spectra of Eu2LTb featured mixed emission including the characteristic bands of Eu(III) and Tb(III). The advantageous features of the complex Eu2LTb opens new possibilities for the future design of bimodal probes and their potential applicability in CEST MR and optical imaging.